Electrochemical Sensor for Food Monitoring Using Metal-Organic Framework Materials - Batoul Hosseinzadeh; Maria Luz Rodriguez-Mendez (Chemosensors, 2023)
Feeding the world’s increasing inhabitants requires considerable quantities of food, whose quality is essential to personal and economic health. Food quality parameters are mandatory to control throughout the fresh produce supply chain to meet consumer requests. Until now, different analytical techniques have been employed in food safety control. However, most of these are laboratory needed, expensive, and time-consuming. To address these obstacles, many researchers have concentrated on developing electrochemical sensors (ECSs) as a powerful method with great sensitivity and reliability for food evaluation. Metal-organic frameworks (MOFs) with surprisingly porous morphology provide uniform yet tunable features, a high specific surface, and established practical applications in various fields. MOF-based ECSs present novel routes for the fast and effective detection of food contaminants or nutrients. In this current review, we concentrate on the MOF-based ECSs for food evaluation by first overviewing the library of available MOF sensors from pristine to MOF-bio composites and then exploiting recent application fields, with an emphasis on how this novel material unlocks new opportunities to monitor food nutrients or hazards.